Adaptor protein Src-homology 2 domain containing E (SH2E) deficiency induces heart defect in zebrafish - Liang Yu-lai; Hu Yang-xi; Li Fang-fang; You Hong-min; Chen Jian; Liang Chun; Guo Zhi-fu; Jing Qing (Acta Pharmacologica Sinica, 2025)
Adaptor proteins play crucial roles in signal transduction across diverse signaling pathways. Src-homology 2 domain-containing E (SH2E) is the adaptor protein highly expressed in vascular endothelial cells and myocardium during zebrafish embryogenesis. In this study we investigated the function and mechanisms of SH2E in cardiogenesis. We first analyzed the spatiotemporal expression of SH2E and then constructed zebrafish lines with SH2E deficiency using the CRISPR-Cas9 system. We showed that homozygous mutants developed progressive pericardial edema (PCE), dilated atrium, abnormal atrioventricular looping and thickened atrioventricular wall from 3 days post fertilization (dpf) until death; inducible overexpression of SH2E was able to partially rescue the PCE phenotype. Using transcriptome sequencing analysis, we demonstrated that the MAPK/ERK and NF-κB signaling pathways might be involved in SH2E-deficiency-caused PCE. This study underscores the pivotal role of SH2E in cardiogenesis, and might help to identify innovative diagnostic techniques and therapeutic strategies for congenital heart disease.